2009
DOI: 10.1111/j.1365-3032.2009.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Ant cues affect the oviposition behaviour of fruit flies (Diptera: Tephritidae) in Africa

Abstract: Although most studies on fruit fly oviposition behaviour focus on horizontal interactions with competitors and cues from host plants, vertical interactions with predators are poorly documented. The present study provides direct evidence indicating that the oviposition behaviour of the two main mango fruit fly species, Ceratitis cosyra (Walker) and Bactrocera invadens Drew-Tsurata & White, is affected by secretions of the dominant arboreal ant Oecophylla longinoda (Latreille). When offered ant-exposed and unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
62
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 30 publications
5
62
1
Order By: Relevance
“…For instance, it has been reported that chemical cues from O. smaragdina deter fruit flies from ovipositing in mangoes on which ants have patrolled [42], and that social bees mark with alarm signals flowers where they have been attacked by a predator [21]. Visual cues also trigger predator avoidance in bees.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been reported that chemical cues from O. smaragdina deter fruit flies from ovipositing in mangoes on which ants have patrolled [42], and that social bees mark with alarm signals flowers where they have been attacked by a predator [21]. Visual cues also trigger predator avoidance in bees.…”
Section: Discussionmentioning
confidence: 99%
“…These behavioural patterns may support the findings of other studies that have found negative associations between ants and some carabids (Niemela et al, 1992;Koivula et al, 1999;Reznikova & Dorosheva, 2004;McColl, 2010). Our findings are also in agreement with other studies that have found that some insects are able to perceive and respond to signals o f ant presence (Offenberg et al, 2004;Oliver et al, 2008;Van Mele et al, 2009). …”
Section: Discussionsupporting
confidence: 93%
“…Most recently, the use the predatory African weaver ant, Oecophylla longinoda (Latreille) has been advocated as a component for inclusion within fruit fly IPM programme in Africa; fruit damage can be reduced as a function of the ant abundance level (van Mele et al, 2007). Furthermore, studies by van Mele et al (2009) showed that semiochemicals deposited on mangoes by O. longinoda masked fruit attractancy and acted as strong avoidance cues, deterring fruit flies from ovipositing on mangoes where the ants had patrolled.…”
Section: Introductionmentioning
confidence: 97%